2008
DOI: 10.1007/s10526-008-9185-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two biological control agents, the weevil Neochetina eichhorniae and the mirid Eccritotarsus catarinensis on water hyacinth, Eichhornia crassipes, grown in culture with water lettuce, Pistia stratiotes

Abstract: The effect of two biological control agents, the weevil Neochetina eichhorniae and the mirid Eccritotarsus catarinensis on water hyacinth, Eichhornia crassipes, grown in culture with water lettuce, Pistia stratiotes Abstract We assessed the effect of two biological control agents, the mirid Eccritotarsus catarinensis (Carvalho) and the weevil Neochetina eichhorniae (Warner), singly or in combination, on the competitive ability of their host plant, water hyacinth, Eichhornia crassipes (Mart.) Solms-Laub., grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The Salvini a weevil ( Cyrtobagous singularis ) has been effective in Australia [200], and several lepidopterans have been effective against milfoil ( Myriophyllum spicatum ; [201]), but large scale applications have been few and new agents and much more research are needed before the technique becomes reliable and cost-effective [202]. …”
Section: Transient Methods Of Wetlands Mosquito Controlmentioning
confidence: 99%
“…The Salvini a weevil ( Cyrtobagous singularis ) has been effective in Australia [200], and several lepidopterans have been effective against milfoil ( Myriophyllum spicatum ; [201]), but large scale applications have been few and new agents and much more research are needed before the technique becomes reliable and cost-effective [202]. …”
Section: Transient Methods Of Wetlands Mosquito Controlmentioning
confidence: 99%
“…Subsequent evaluations have demonstrated that it affects water hyacinth growth (Coetzee et al, 2007) and competitive ability (Coetzee et al, 2005;Ajuonu et al, 2009), by reducing the plant's overall vigour. Eccritotarsus catarinensis has also been released in Zimbabwe, Zambia, Malawi, Benin, and China but only established in Malawi (Coetzee et al, 2009a).…”
Section: Orthogalumna Terebrantismentioning
confidence: 99%
“…In warmer regions worldwide different ways of controlling the populations of water lettuce are used including chemical and physical methods, but no reports about total local eradication could be found (Cilliers et al 1996, Diop and Hill 2009, Gherardi et al 2011. Mitigation by biological control agents could be more successful (Cilliers et al 1996, Ajuonu et al 2009, Diop and Hill 2009, Baker et al 2010, with the introduction of new competitive alien species, which might on the other hand, have additional impacts (usually negative) on native biodiversity (Lockwood et al 2007).…”
Section: Introductionmentioning
confidence: 99%